Ahmad Dahlan's Thoughts on Education as a Means of Empowering the People - Muaddyl Akhyar; Ilpi Zukdi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study examines Ahmad Dahlan's thoughts on education as a means of community empowerment and social transformation. Ahmad Dahlan, the founder of the Muhammadiyah organization, viewed education as the primary tool to liberate Muslims from ignorance, backwardness, and social injustice. His educational approach integrated religious and general sciences while providing practical skills relevant to societal needs. This research employs a descriptive qualitative approach with a literature study to explore Ahmad Dahlan's educational concepts and their application in community empowerment. The findings reveal that Ahmad Dahlan emphasized inclusive education, ensuring access for all social groups, including the poor and women, while focusing on the development of individuals with strong social and moral awareness. In his perspective, education functions as an agent of social change, fostering a more just, prosperous, and civilized society. Rooted in Islamic values, his educational model remains relevant in addressing modern educational challenges.